A negative electrode material for sodium battery

By using composite material particles in the sodium battery negative electrode material, combining carbon matrix, graphite particles and nanoactive particles, and setting a modified layer outside the spherical graphite, the electrode structure disintegration problem caused by volume expansion during charging and discharging in the prior art is solved, and a high capacitance and high temperature life are achieved.

CN115881921BActive Publication Date: 2025-03-14NAYUE NEW ENERGY (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211720924.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-14
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The volume of existing sodium battery negative electrode materials expands too much during charging and discharging, resulting in the disintegration of the electrode structure and the decrease in capacitance and capacitance life.

Method used

A plurality of electrode composite particles are used, including a core layer composed of a carbon matrix, graphite particles and nanoactive particles. The graphite particles include spherical and plate-shaped graphite. The nanoactive particles are covered with a protective layer and a modified layer is provided outside the spherical graphite.

Benefits of technology

The high capacitance and high temperature life of the negative electrode material of sodium battery are achieved, while avoiding electrode structure rupture and extending the service life of the rechargeable battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115881921B_ABST
    Figure CN115881921B_ABST
Patent Text Reader

Abstract

The invention discloses a sodium battery negative electrode material, comprising: a plurality of electrode composite material particles; the electrode composite material particles, comprising: a core layer; the core layer comprising: a carbon matrix; a plurality of graphite particles, the plurality of graphite particles comprising spherical graphite and plate-like graphite, the weight ratio of spherical graphite to plate-like graphite is not less than 1:1, and the ratio of the average particle size (D50) of spherical graphite to plate-like graphite is 1:(0.3-0.6); a plurality of nanometer active particles, the plurality of nanometer active particles are distributed in the carbon matrix; wherein the nanometer active particles comprise a nanometer active material and a protective layer coated outside the nanometer active material, the protective layer being an oxide, nitride or carbide of the nanometer active material. The invention can take into account the high capacity of the sodium battery negative electrode material and the requirement of not being easy to break, and can improve the high temperature life of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium battery negative electrode materials, and in particular to a sodium battery negative electrode material. Background Art

[0002] The active material of the negative electrode material of sodium batteries is mostly made of graphite, but because graphite has a low capacity and a low high temperature life, there is further development to use high capacity materials or a composite of high capacity materials and graphite as the material of the negative electrode.

[0003] The high-capacity materials commonly used at present are silicon or metal oxides, but the volume of silicon and metal oxides will expand too much during the charging and discharging process, causing the electrode structure to collapse. After a certain number of charge and discharge cycles, the capacity and capacitance life of the rechargeable battery will drop significantly. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a negative electrode material for a sodium battery.

[0005] The present invention discloses a sodium battery negative electrode material, comprising: a plurality of electrode composite material particles;

[0006] The electrode composite material particles include: a core layer;

[0007] The core layer comprises:

[0008] Carbon matrix;

[0009] A plurality of graphite particles, wherein the plurality of graphite particles are distributed in a carbon matrix; the plurality of graphite particles include spherical graphite and plate-like graphite, wherein the weight ratio of the spherical graphite to the plate-like graphite is not less than 1:1, and the ratio of the average particle size (D50) of the spherical graphite to the plate-like graphite is 1:(0.3-0.6);

[0010] A plurality of nano-active particles are distributed in a carbon matrix; wherein the nano-active particles include a nano-active material and a protective layer coated outside the nano-active material, and the protective layer is an oxide, a nitride or a carbide of the nano-active material.

[0011] As a further improvement of the present invention, the carbon matrix is ​​amorphous carbon or nitrided amorphous carbon.

[0012] As a further improvement of the present invention, the spherical graphite is spherical natural graphite, the plate-like graphite is plate-like artificial graphite, and the spherical natural graphite is provided with a modified layer.

[0013] As a further improvement of the present invention, the weight ratio of the spherical graphite to the plate-like graphite is 1:1 to 9:1.

[0014] As a further improvement of the present invention, the weight ratio of the spherical graphite to the plate-like graphite is 4:1.

[0015] As a further improvement of the present invention, the modified layer is an asphalt modified layer, which is prepared by coating coal-based asphalt or petroleum-based asphalt on spherical natural graphite and heat treating it at a temperature of 800°C to 1000°C for 8 to 12 hours.

[0016] As a further improvement of the present invention, the mass ratio of the spherical natural graphite to asphalt is (95-99):(1-5).

[0017] As a further improvement of the present invention, the particle size of the electrode composite material particles is 500 nanometers to 40 micrometers, and the particle size of the spherical graphite is 300 nanometers to 30 micrometers.

[0018] As a further improvement of the present invention, the nano-active material includes but is not limited to one of silicon, silver, zinc, aluminum, arsenic, and iron, the particle size of the nano-active particles is 1 nanometer to 500 nanometers, and the thickness of the protective layer is less than or equal to 10 nanometers.

[0019] As a further improvement of the present invention, the electrode composite material particles further include: a shell layer;

[0020] The shell layer covers the surface of the core layer, and the Mohs hardness of the shell layer is higher than 2.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention combines graphite with nano-active materials and coats the nano-active materials with a protective layer, so that the negative electrode materials of sodium batteries can meet the requirements of high capacity and not easy to break.

[0023] The present invention can improve the high temperature life of the negative electrode material by compounding graphites of different particle sizes, different morphologies and different properties; and a modified layer is provided on the outer layer of the spherical natural graphite, which can further improve the high temperature life of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic diagram of the structure of the negative electrode material for a sodium battery disclosed in the present invention;

[0025] Figure 2 Another structural schematic diagram of the sodium battery negative electrode material disclosed in the present invention;

[0026] Figure 3 The figure is a comparison chart of the relative capacity test results of the embodiment of the present invention and the comparative example.

[0027] In the figure:

[0028] 1. Carbon matrix; 2. Spherical graphite; 3. Plate graphite; 4. Modified layer; 5. Nano-active material; 6. Protective layer. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0031] like Figure 1 As shown, the present invention provides a sodium battery negative electrode material, which is coated on a conductive carrier to form a sodium battery negative electrode; the negative electrode material comprises: a plurality of electrode composite material particles; wherein,

[0032] The electrode composite material particles of the present invention include: Figure 1 The core layer shown; the core layer includes: a carbon matrix 1, a plurality of graphite particles and a plurality of nano-active particles, the plurality of graphite particles are distributed in the carbon matrix 1, the plurality of graphite particles include spherical graphite 2 and plate-like graphite 3; a plurality of nano-active particles are distributed in the carbon matrix 1, the nano-active particles include a nano-active material 5 and a protective layer 6 coated on the outside of the nano-active material 5, the protective layer 6 is an oxide, nitride or carbide of the nano-active material 5.

[0033] Specific:

[0034] The carbon matrix 1 of the present invention includes but is not limited to amorphous carbon or nitrided amorphous carbon;

[0035] The spherical graphite 2 of the present invention is preferably spherical natural graphite, and the plate-like graphite 3 is preferably plate-like artificial graphite; the weight ratio of the spherical graphite 2 to the plate-like graphite 3 is not less than 1:1, preferably 1:1 to 9:1, and more preferably 4:1; the particle size of the spherical graphite is 300 nanometers to 30 micrometers, and the ratio of the average particle size (D50) of the spherical graphite 2 to the plate-like graphite 3 is 1:(0.3 to 0.6). The present invention can improve the high-temperature life characteristics of the negative electrode active material composed of spherical graphite 2 and plate-like graphite 3; when it exceeds the above range, it is difficult to exert excellent high-temperature life characteristics.

[0036] The nano active material 5 of the present invention includes nano particles of IVA group elements or transition metals, preferably one of silicon, silver, zinc, aluminum, arsenic, and iron; thus, the high capacity required by the rechargeable battery can be provided. In each nano active particle, the volume percentage of the protective layer 6 in the nano active particle is less than 23.0%. Therefore, when the volume of the nano active material 5 expands due to battery charging, the protective layer 6 provides a buffering effect to prevent the nano active material 5 from squeezing the surrounding carbon matrix 1 and causing the electrode composite material particles to rupture. In addition, since the volume ratio of the protective layer 6 to the entire nano active particle is controlled within an appropriate range, it helps to avoid the impedance increase and capacitance decrease of the electrode composite material particles due to the excessive thickness of the protective layer 6, thereby taking into account the high capacitance and non-rupture requirements of the electrode composite material particles.

[0037] The particle size of the electrode composite material particles of the present invention is 500 nanometers to 40 micrometers. Thus, it can be ensured that the electrode plate made of the electrode composite material particles has good compaction density, structural strength and high coulomb efficiency, which helps to increase the service life of the rechargeable battery. Electrode composite material particles with a particle size of less than 500 nanometers have too high a specific surface area, which will lead to a decrease in coulomb efficiency. The electrode plate made of electrode composite material particles with a particle size greater than 40 micrometers has insufficient structural strength, and its service life decay rate will be greatly increased.

[0038] The particle size of each nano-active particle of the present invention is 1 nanometer to 500 nanometers; thus, it can be ensured that the nano-active particles meet the requirements of not being easy to break and providing sufficient capacitance. The thickness of the protective layer 6 of each nano-active particle is less than or equal to 10 nanometers. Thus, it helps to avoid the increase in impedance and decrease in capacitance of the electrode composite material particles due to the excessive thickness of the protective layer 6, thereby meeting the requirements of high capacitance and not being easy to break of the electrode composite material particles.

[0039] The total volume ratio of the nano-active particles to the carbon matrix 1 and the graphite particles of the present invention is 1:9 to 9:1, thereby allowing the electrode composite material particles to have a high capacitance. Furthermore, the volume of the graphite particles is greater than the volume of the nano-active particles, thereby helping to buffer the effect of the volume change of the nano-active particles on the structure of the electrode composite material particles.

[0040] The electrode composite material particles of the present invention further include a shell layer (not shown in the figure), which covers the surface of the core layer. The shell layer is a metal or ceramic with a Mohs hardness higher than 2.

[0041] like Figure 2 As shown, the present invention provides a sodium battery negative electrode material, Figure 1The difference between the scheme shown is that the present invention can also be provided with a modified layer 4 outside the spherical natural graphite, and the modified layer is prepared by coating coal-based asphalt or petroleum-based asphalt on the spherical natural graphite and heat treating it at a temperature of 800°C to 1000°C for 8 to 12 hours, and the preferred heat treatment time is 10 hours; the mass ratio of spherical natural graphite to asphalt is (95 to 99):(1 to 5), preferably 97:3.

[0042] The present invention can further improve the high temperature life characteristics by using spherical graphite whose surface is modified to pitch as the cathode active material.

[0043] Embodiment: The present invention verifies the influence of the combination of different graphite particles on the performance based on the same nano-active particles; wherein, the particle size of the nano-active particles involved in the following embodiment is 200nm, the thickness of the protective layer is 5nm, the total volume ratio of the nano-active particles to the carbon matrix and the graphite particles is 1:2, the particle size of the electrode composite material particles is 20 microns, the nano-active material 5 is a nano-silicon core, and the protective layer 6 is a silicon oxide film.

[0044] Embodiment 1:

[0045] The negative electrode material of this embodiment 1 is a mixture of spherical natural graphite (D50: 1 micron) and plate-shaped artificial graphite (D50: 0.4 micron) in a mass ratio of 9:1. The negative electrode material, conductive agent and binder are made into negative electrode sludge, which is then coated on a 10 micron thick copper foil to produce a negative electrode with a loading capacity of 1 mAh / cm 2 cathode.

[0046] Embodiment 2:

[0047] Different from Example 1, the negative electrode material of Example 2 is a mixture of spherical natural graphite (D50: 1 micron) and plate-like artificial graphite (D50: 0.4 micron) in a mass ratio of 8:2.

[0048] Embodiment 3:

[0049] Different from Example 1, the negative electrode material of Example 3 is a mixture of spherical natural graphite (D50: 1 micron) and plate-like artificial graphite (D50: 0.4 micron) in a mass ratio of 5:5.

[0050] Embodiment 4:

[0051] Different from Example 2, the spherical natural graphite selected in the negative electrode material of this Example 4 is coated with an asphalt modification layer, and the modification method is: a mixture of spherical natural graphite and petroleum asphalt in a mass ratio of 97:3 is heat-treated at 900°C for 10 hours.

[0052] Comparative Example 1:

[0053] Different from Example 1, the negative electrode material of Comparative Example 1 is a mixture of spherical natural graphite (D50: 1 micron) and plate-like artificial graphite (D50: 0.4 micron) in a mass ratio of 1:5.

[0054] Comparative Example 2:

[0055] Different from Example 1, the negative electrode material of Comparative Example 1 is a mixture of spherical natural graphite (D50: 1 micron) and plate-like artificial graphite (D50: 0.2 micron) in a mass ratio of 9:1.

[0056] Comparative Example 3:

[0057] Different from Example 1, the negative electrode material of Comparative Example 1 is a mixture of spherical natural graphite (D50: 1 micron) and plate-like artificial graphite (D50: 0.8 micron) in a mass ratio of 9:1.

[0058] Relative capacity tests were performed on Examples 1 to 4 and Comparative Examples 1 to 3. The test results are as follows: Figure 3 As shown; in the figure, curves S1 to S4 correspond to embodiments 1 to 4, and curves D1 to D3 correspond to corresponding examples 1 to 3.

[0059] According to the test results, Example 4 is the best solution of the present invention.

[0060] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium battery negative electrode material, characterized in that: include: a plurality of electrode composite particles; The electrode composite material particles include: a core layer; The core layer comprises: Carbon matrix; A plurality of graphite particles, wherein the plurality of graphite particles are distributed in a carbon matrix; the plurality of graphite particles include spherical graphite and plate-like graphite, wherein the weight ratio of the spherical graphite to the plate-like graphite is 4:1, and the ratio of the average particle size (D50) of the spherical graphite to the plate-like graphite is 1:(0.3-0.6); wherein the spherical graphite is spherical natural graphite, the plate-like graphite is plate-like artificial graphite, the spherical natural graphite is provided with a modified layer, the modified layer is an asphalt modified layer, and the modified layer is prepared by coating coal-based asphalt or petroleum-based asphalt on the spherical natural graphite and heat treating the spherical natural graphite at a temperature of 800° C. to 1000° C. for 8 to 12 hours; A plurality of nano-active particles are distributed in a carbon matrix; wherein the nano-active particles include a nano-active material and a protective layer coated outside the nano-active material, and the protective layer is an oxide, a nitride or a carbide of the nano-active material.

2. The sodium battery negative electrode material according to claim 1, characterized in that: The carbon matrix is ​​amorphous carbon or nitrided amorphous carbon.

3. The sodium battery negative electrode material according to claim 1, characterized in that The mass ratio of the spherical natural graphite to the asphalt is (95-99):(1-5).

4. The sodium battery negative electrode material according to claim 1, characterized in that The particle size of the electrode composite material particles is 500 nanometers to 40 micrometers, and the particle size of the spherical graphite is 300 nanometers to 30 micrometers.

5. The sodium battery negative electrode material according to claim 4, characterized in that: The nano active material includes but is not limited to one of silicon, silver, zinc, aluminum, arsenic, and iron. The particle size of the nano active particles is 1 nanometer to 500 nanometers. The thickness of the protective layer is less than or equal to 10 nanometers.

6. The sodium battery negative electrode material according to claim 1, characterized in that: The electrode composite material particles further include: a shell layer; The shell layer covers the surface of the core layer, and the Mohs hardness of the shell layer is higher than 2.

Citation Information

Patent Citations

  • Electrode composite material, manufacturing method of electrode composite material and rechargeable battery electrode

    CN113745471A

  • Negative active material for lithium secondary battery and lithium secondary battery using same

    KR1020110042840A